Transformational Leadership and Job Satisfaction in Employee Performance: Kepemimpinan Transformasional dan Kepuasan Kerja pada Kinerja Karyawan - Hutagaluh, Gigih; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2024)
Background: In a competitive business environment, organizations need strong capabilities to succeed globally. Specific Background: Employee performance is essential for organizational success, influenced by leadership, job satisfaction, and commitment. Knowledge Gap: Limited research has examined the combined effects of these factors in a specific context. Aims: This study explores the relationships among transformational leadership, job satisfaction, and organizational commitment on employee performance at PT. Tirtadaya Adiperkasa Gempol. Results: A quantitative approach utilizing a Likert scale questionnaire and Simple Random Sampling revealed that transformational leadership, job satisfaction, and organizational commitment significantly enhance employee performance both individually and collectively. Novelty: This research addresses a critical gap in the literature regarding the interaction of these factors. Implications: The findings highlight the importance of nurturing transformational leadership and improving job satisfaction and organizational commitment as effective strategies to boost employee performance, offering organizations a pathway to gain competitive advantages. Highlights : Transformational leadership significantly enhances employee motivation and productivity. Job satisfaction plays a crucial role in fostering organizational commitment. Collective influence of leadership, satisfaction, and commitment boosts overall performance. Keywords: Transformational Leadership, Job Satisfaction, Organizational Commitment, Employee Performance, Quantitative Research